The esteem needs in the main character of ‘Me Before You’ movie - Diana Anggraeni; Herland Franley Manalu; Desty Anggraini (Studies in English Language and Education, 2021)
Humans have gone through many incidents, both good and bad experiences, and sometimes these experiences are shared with others in the form of stories. The stories, as one of the forms of literary works, would be nothing without the created characters within them because they provide the viewers with a purpose and a reason for us to learn about what happens in the story. Besides, they act as one important element in the movie with various psychological effects. This research aims to analyze the characteristics and the hierarchy of human needs, especially esteem needs, that appear in the main character named Will Traynor in the ‘Me Before You’ movie directed by Thea Sharrock. This study uses descriptive data analysis which describes a phenomenon and the main character in the movie. The results revealed seven characters comprising the esteem needs hierarchy: sensitive, open-minded, friendly, kind, confident, humble, and stubborn. The esteem needs hierarchy is the desire to have the need to be approved, valued, and recognized to have some self-esteem. This is striking in the movie because of the status of the character, Will Traynor as a lord, and Louisa Clark who is only a maid and has no superiority over Will in her life. The findings imply the personality of humans differ in their characters and psychology as shown from the esteem needs hierarchy in Will’s personality expressing the different types of characteristics.